Larvicidal Activities of Different Parts of Melia azedarach Linn. against Culex quinquefasciatus Say. (Diptera: Culicidae) - Ilahi, Ikram; Khan, Imran; Tariq, Mohammad; Ahmad, Izhar (Journal of Basic & Applied Sciences, 2012)
Melia azedarach is a perennial tree, belongs to the family Meliaceae, and locally known as Tora Shandi in Swat and Dir regions of Khyber Pukhtunkhwa (K.P.K). The present study was aimed to evaluate the larvicidal activity of aqueous extracts of different parts of Melia azedrach against Culex quinquefasciatus. Various concentrations (50, 100, 500, 1000, 1500 and 2000 ppm) of aqueous extracts of leaves, fruits and bark of Melia azedarach were tested for larvicidal activity against Culex quinquefasciatus. There occurred a continuous increase in mortality of 3rd and 4th instar larvae with increase in concentration of the extracts. At 50ppm, the fruit extract caused 1.6 + 2.2 % mortality, leaves extract 17.60 + 6.0 % and bark extract caused 17.60 + 7.3 % mortality. The LC50 value for fruits extract was 2035.13ppm, leaves extract 612.250ppm and for bark extract 368.3ppm. Among the aqueous extracts of fruits, leaves and bark, the aqueous extract of bark was proved to be more toxic and an efficient larvicidal against Culex quinquefasciatus. The findings of the present study indicate that the aqueous extract of the bark of Melia azedarach of Dir region of khyber pakhtunkhwa can serve as a good source of preparations for pest control especially mosquito control.